2015
DOI: 10.21608/hjsc.2015.6476
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nitrate Content in Response to Salicylic Acid in Spinach and Parsley Fertilized with Two Different N-Sources

Abstract: Spinach and parsley are hyper-nitrate accumulator vegetables, thereby constituting a possible human health risk. For that, pot and two field experiments were conducted to investigate the effect of exogenous salicylic acid (SA) application on yield, nitrate content and another quality parameters in spinach and parsley using two different ammonium fertilizers as ammonium sulfate (A. sulfate) and urea. The results of pot experiment (factorial, 2 x 2) showed that, A. sulfate-fertilized plants produced maximum yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Ammonium sulfate is a nitrogen fertilizer that contains sulfur (21%) (Berhe et al, 2019). Elwan and Elhamahmy (2015) reported that combination of UreaZA fertilizers had a positive interaction effect on plant growth. UreaZA fertilizers contain N nutrient needed for plant growth and photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium sulfate is a nitrogen fertilizer that contains sulfur (21%) (Berhe et al, 2019). Elwan and Elhamahmy (2015) reported that combination of UreaZA fertilizers had a positive interaction effect on plant growth. UreaZA fertilizers contain N nutrient needed for plant growth and photosynthesis.…”
Section: Introductionmentioning
confidence: 99%